TRADISI DAN KELEMBAGAAN MASYARAKAT DALAM PENGELOLAAN SUMBERDAYA PESISIR DAN LAUT DI KOTA TIDORE KEPULAUAN PROVINSI MALUKU UTARA - Tawari, Ruslan Husen Saban; Paillin, J. B.; Haruna, Haruna; Siahainenia, Stany; Sangadji, Selfi; Angkotasan, Abdul (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2020)
Increasing of global awareness related to environmental management, ecosystems, and fisheries resources is a trigger in the reactualization of community traditions and institutions. People of Tidore Islands City, known as indigenous people with their coastal and marine institutional traditions in North Maluku Province, have a local order handed down in the utilization of the coastal and marine resources. This study aimed to analyze the existence of traditions and institutions and their effects on managing coastal and marine resources in the City of Tidore Islands. The research was conducted on June-August 2019 in the city of Tidore Islands. This research encompass 4 Subdistrict and 2 villages namely, Tomalou, Mareku, Soasio and Dowora Subdistrict as well as Mare Gam and Maitara village,. The research applied a qualitative method, which involves in-depth interview techniques, observation, and documentation. Data were analysed using a qualitative descriptive analysis. The results of the study showed that there are five local wisdoms that are maintained by the people of Tidore Islands City nowadays. These local wisdom is a legacy from the ancestors in the management of coastal and marine resources, namely Karo Kahiya (Calling the Dolphins), Fola Sow (Lit. House of Medicine), Jere (Sacred), Cofa (Fish breeding) and Saihu (Leader/Fishing Master). The approach to management of coastal and marine resources with procedures or traditions and institutions contributed a significant impact (very effective) on local communities in relation to the sustainable use of coastal and marine resources. as well as the preservation of local traditions and customary institutions. ABSTRAK Meningkatnya kesadaran global terkait pengelolaan lingkungan, ekosistem dan pemanfaatan sumberdaya perikanan menjadi pemicu dalam reaktualisasi tradisi dan kelembagaan masyarakat. Masyarakat Kota Tidore Kepulauan yang dikenal sebagai masyarakat adat dengan tradisi kelembagaan pesisir dan lautnya di Provinsi Maluku Utara, merupakan masyarakat yang memiliki tatanan lokal yang turun temurun dalam pemanfaatan sumberdaya pesisir dan laut dimaksud. Penelitian ini bertujuan untuk menganlisis eksistensi tradisi dan kelembagaan serta pengaruhnya terhadap pengelolaan sumberdaya pesisir dan laut di Kota Tidore Kepulauan. Penelitian ini dilaksanakan pada Juni- Agustus 2019, di Kota Tidore Kepulauan meliputi 2 desa dan 4 kelurahan yakni, Desa Mare Gam, Desa Maitara, Kelurahan Tomalou dan Kelurahan Mareku, Kelurahan Soasio dan kelurahan Dowora. Penelitian ini merupakan penelitian kualitatif, yang melibatkan teknik-teknik wawancara mendalam, observasi, dan dokumentasi. Analisis data dilakukan secara deskriptif kualitatif. Hasil Penelitian menunjukkan sampai saat ini masih terdapat lima kearifan lokal yang tetap terjaga oleh masyarakat Kota Tidore Kepulauan yang merupakan warisan dari para leluhur dalam pengelolaan sumbedaya pesisir dan laut, yakni Karo Kahiya (Memanggil Lumba Lumba), Fola Sow (Rumah Obat), Jere (Keramat), Cofa (Penangkaran Ikan) dan Saihu (Pemimpin/Nakoda dalam Operasi Penangkapan Ikan). Pendekatan pengelolaan sumberdaya pesisir dan lautan dengan tradisi dan kelembagaan telah memberikan dampak yang sangat signifikan (sangat efektif) bagi masyarakat setempat dalam pemanfaatan sumberdaya pesisir dan lautan yang berkelanjutan maupun pelestarian tradisi dan kelembagaan adat istiadat setempat. Kata Kunci: Tradisi, kelembagaan, pengelolaan, sumberdaya, Tidore